Biomechanical gait analysis in sheep: kinematic parameters - Silva, Bruna; João, Filipa; Amado, Sandra; Alvites, Rui D.; Maurício, Ana C.; Esteves, Bárbara; Sousa, Ana C.; Lopes, Bruna; Sousa, Patrícia; Dias, Juliana R.; Veloso, António; Pascoal-Faria, Paula; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Animals have been used as models to help to better understand biological and anatomical systems, and pathologies in both humans and non-human species, and sheep are often used as an in vivo experimental model for orthopedic research. Gait analysis has been shown to be an important tool in biomechanics research with clinical applications. The purpose of this study was to perform a kinematic analysis using a tridimensional (3D) reconstruction of the sheep hindlimb. Seven healthy sheep were evaluated for natural overground walking, and motion capture of the right hindlimb was collected with an optoelectronic system while the animals walked in a track. The analysis addressed gait spatiotemporal variables, hip, knee and ankle angle and intralimb joint angle coordination measures during the entire walking cycle. This study is the first that describes the spatiotemporal parameters from the hip, knee and ankle joints in a tridimensional way: flexion/extension; abduction/adduction and inter/external rotation. The results of this assessment can be used as an outcome indicator to guide treatment and the efficacy of different therapies for orthopedic and neurological conditions involving the locomotor system of the sheep animal model.